Is the goodwill recognised in a business combination an indicator of the future profitability of the combined company? - Janowicz, Magdalena; Luty, Piotr (Czy wartość firmy ujawniona po połączeniu spółek wskazuje na przyszłą rentowność połączonej jednostki?, 2019)
The aim of the paper is to determine if there is any link between goodwill recognised in a business combination and the future performance of the combined company. The authors focused on examining the effects that business combinations had on the profitability of selected companies, performing a statistical analysis of their financial results. The study covered 730 Polish companies participating in a merger process (the acquiring company was examined at the time of the merger and 3 years after the merger date). The research included companies disclosing positive goodwill (99 companies) and not disclosing it (631 companies). The research period covered mergers in the years 2007-2012. The profitability analysis for 3 years after the merger covered the period until 2015. The result of the empirical research shows that the companies which recognised goodwill during the merger process were more profitable in the examined period of time. The study contributes to a wide research area focusing on examining the effects of business combinations on the future efficiency of combined companies
Financial Sciences. Nauki o Finansach, 2019, vol. 24, no. 4, s. 45-54
Keywords: mergers and acquisitions; business combination; goodwill; efficiency; profitability; fuzje i przejęcia; połączenia spółek; wartość firmy; efektywność działania; zyskowność